2021
DOI: 10.1177/2150135120978766
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Quality of Life in Children With Anomalous Aortic Origin of a Coronary Artery

Abstract: Background: Anomalous aortic origin of a coronary artery (AAOCA) is associated with sudden death in the young. We sought to determine quality of life (QOL) in patients/families affected by AAOCA. Methods: Patients with AAOCA (8-18 years) were prospectively included from January 2016 to May 2017. Parent proxy and patient Pediatric Cardiac Quality of Life Inventory (PCQLI) were used to evaluate QOL and Pediatric Quality of Life Inventory (PedsQL) Family Impact Module to assess the impact of AAOCA on families, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
4
2
Order By: Relevance
“…Our results of good QoL after ACAOS repair are consistent with these previous reports. Contrary to our findings, Agrawal et al reported a decreased QoL in children and adolescents with ACAOS as perceived by patients and caregivers independently of surgical status ( 40 ). In their study most patients were unoperated at the time of the questionnaire which may explain their different results ( 40 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results of good QoL after ACAOS repair are consistent with these previous reports. Contrary to our findings, Agrawal et al reported a decreased QoL in children and adolescents with ACAOS as perceived by patients and caregivers independently of surgical status ( 40 ). In their study most patients were unoperated at the time of the questionnaire which may explain their different results ( 40 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our findings, Agrawal et al reported a decreased QoL in children and adolescents with ACAOS as perceived by patients and caregivers independently of surgical status ( 40 ). In their study most patients were unoperated at the time of the questionnaire which may explain their different results ( 40 ). In our study, based on the QoL questionnaire analysis, we did not discern any negative impact of heart surgery experience.…”
Section: Discussioncontrasting
confidence: 99%
“…It is now evident that the diagnosis of AAOCA may have a negative effect on the quality of life of either the patient, the parents, or both, impacting families’ functioning. 29 Also, medical management often is associated with the alteration of parents’ perception of their child's health. 30 For these reasons, consideration of surgical management of AAOCA is currently expanding toward younger ages.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 10 , 11 Patient/family anxiety also play a large role in surgical decision making given that patients have led largely healthy lives up to their diagnosis, and the emotional influence of this unexpected life change certainly take a toll. 12 …”
mentioning
confidence: 99%